Exploring anterion capsular contraction syndrome in cataract surgery: insights into pathogenesis, clinical course, influencing factors, and intervention approaches - Lin, Xuanqiao; Ma, Dongmei; Yang, Jin (Frontiers in Medicine, 2024)
Anterior Capsular Contraction Syndrome (ACCS) is a challenging complication that can occur following phacoemulsification cataract surgery. Characterized by capsular bag wrinkling, intraocular lens (IOL) decentration and tilt, ACCS can have negative effects on visual outcomes and patient satisfaction. This review aims to investigate the pathogenesis, clinical course, influencing factors, and intervention approaches for ACCS after cataract surgery. By understanding the underlying mechanisms and identifying factors that contribute to ACCS, surgeons can enhance their ability to predict and manage this complication. Various intervention strategies are discussed, highlighting their importance in reducing complications and improving surgical outcomes. However, further research is needed to determine optimal prevention and management strategies through long-term follow-up and comparative analyses. Advancements in this field will ultimately lead to improved visual outcomes and optimized cataract surgery for patients.